Respostas
respondido por:
1
3 (t - 5) + 7t = 5 (3- t)
3t - 15 + 7t = 15 - 5t
3t + 7t + 5t = 15 + 15
15t = 30
t = 30/15
t = 2
3t - 15 + 7t = 15 - 5t
3t + 7t + 5t = 15 + 15
15t = 30
t = 30/15
t = 2
respondido por:
0
3 (t-5)+7t=5 ( 3-t)
3t -15 + 7t = 5 ( 3-t)
3t -15 + 7t = 15 - 5t
3t -15 + 7t + 5t = 15
3t + 7t + 5t = 15 + 15
3t + 7t + 5t = 30
10t + 5t = 30
15t = 30
t = 30 / 15
t = 2
3t -15 + 7t = 5 ( 3-t)
3t -15 + 7t = 15 - 5t
3t -15 + 7t + 5t = 15
3t + 7t + 5t = 15 + 15
3t + 7t + 5t = 30
10t + 5t = 30
15t = 30
t = 30 / 15
t = 2
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás